Existence of Three Monotone Solutions of Nonhomogeneous Multipoint BVPs for Second-Order Differential Equations. (27th July 2008) - Liu, Xingyuan
Abstract : This paper is concerned with nonhomogeneous multipoint boundary value problems of second-order differential equations with one-dimensionalp -Laplacian. Sufficient conditions to guarantee the existence of at least three solutions (may be not positive) of these BVPs are established.